Lipid profile is associated with decreased fatigue in individuals with progressive multiple sclerosis following a diet-based intervention: Results from a pilot study - Fellows Maxwell, Kelly (PLoS One, 2019)
PURPOSE: To investigate associations between lipid profiles and fatigue in a cohort of progressive multiple sclerosis (MS) patients on a diet-based multimodal intervention. METHODS: This pilot study included 18 progressive MS patients who participated in a prospective longitudinal study of fatigue following a diet-based multimodal intervention that included exercise, neuromuscular electrical stimulation and stress reduction. The diet recommended high intake of vegetables and fruits, encouraged consumption of animal and plant protein and excluded foods with gluten-containing grains, dairy and eggs. Fatigue was measured on the Fatigue Severity Scale (FSS) at baseline and every 3 months for 12 months. A lipid profile consisting of high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC) and triglycerides (TG) was obtained on fasting blood samples at baseline and 12 months. RESULTS: FSS scores decreased from a baseline of 5.51 (95% CI: 4.86, 6.16) to a mean of 3.03 (95% CI: 2.23, 3.82) at 12 months (p < 0.001). At 12 months, increases in HDL-C (mean change: +6.0 mg/dl; 95% CI: 0.3, 12.0; p = 0.049) and decreases in BMI (mean change: -2.6 kg/m(2); 95% CI: -3.6, -2.5; p < 0.001), LDL-C (mean change: -10.4 mg/dl; 95% CI:-19.7, -1.2; p = 0.029), TG (mean change: -29.2 mg/dl; 95% CI: -44.3, -14.2; p = 0.001), TG to HDL-C ratio (mean change: -0.6; 95% CI: -1.0, -0.3; p = 0.002) and TC to HDL-C ratio (mean change:-0.6; 95% CI: -1.0, -0.3; p = 0.003) were observed compared to baseline. Improvements in FSS were associated with increases in HDL-C (β = -0.05; 95% CI: -0.1, -0.0004; p = 0.048) and changes in TC (p = 0.005) from baseline to 12 months. CONCLUSIONS: Lipid profile variables are associated with improvements in fatigue in progressive MS patients on a diet-based multimodal intervention.